Study of a Photovoltaic Solar Pumping System for Irrigation: Case of the Adaraoua Site - SALEY MOUSSA , Ahmed Roufaï; ALI, Aboubacar; BOUKAR, Makinta; MADOUGOU, Saïdou (European Journal of Applied Sciences, 2022)
This work presents a study of a photovoltaic solar pumping system for the irrigation of a plot of 6,500 m2 in the village of ADARAOUA. The purpose of this study is to bring a contribution to the population of village in their market gardening through the use of photovoltaic (PV) solar energy. Using this energy, it is possible to pump water to a certain depth from wells or boreholes by a solar pump. The system set up comprises four main parts, namely a PV generator with a peak power (Pc) of 1,235.47 Wp, a solar pump of the GRUNDFOS SQFLEX type with a power of 1.4 kW, a control box (FAMATEL) and a well 15 m deep. On the economic level, although the realization of the system requires a significant cost of 3,974,600 F, one can retain as advantages a very low maintenance cost, and a satisfactory profitability of the cultures. From a technical point of view, the solar PV pumping system is very reliable, efficient and autonomous. It is applicable for any need and in any area of ​​the country (Niger) thanks to the solar deposit which is very important, the average value of which can exceed 7 kWh/m2/d. These are the advantages that make it one of the most suitable systems for irrigation in rural areas from a technical and economic point of view.